Demographic and Clinical Profile of Women Attending Genetic Clinic for Prenatal Invasive Testing at a Tertiary Referral Center, India - Koirala, N.; Kafle, S. P. (Kathmandu University Medical Journal, 2021)
Background The Prenatal Invasive Tests (PIT) are used during pregnancy for the detection of genetic anomalies. Studies addressing the profile of women who come to seek prenatal invasive testing are scarce. Objective To assess the socio-demographic characteristics and clinical profile of women who are referred for prenatal invasive testing in a tertiary referral center in India. Method A descriptive, cross-sectional study was undertaken in 60 women who came to the genetic clinic at a tertiary referral center, New Delhi, India following counseling regarding prenatal invasive testing. Data was collected using a self-developed and validated semi-structured questionnaire, administered after the counseling for the test by the counselor. Data were analyzed using mean, percentage, standard deviation and range. Result The majority of the women were from urban residences and all of them were literate. Nearly half of the women were in the age group 21-30 years. Mean gestational age was 19.24 ± 2.63 weeks and most were pregnant for the second time. The main reasons for referral were advanced maternal age and abnormal obstetric ultrasonography. The participant’s understanding of the test was still incomplete despite the counseling and there was a need for additional counseling/information. One-third of them preferred additional counseling whereas, the remaining twothirds preferred booklets and pamphlets. Conclusion The profiles of pregnant women referred to genetic clinic provide better insight about their background for the health personnel and this study emphasizes rechecking the understanding regarding invasive tests following counseling; which eventually helps for appropriate decision making regarding the tests.